The intricate dance of non-coding RNAs in myasthenia gravis pathogenesis and treatment - Wang, Benqiao; Zhu, Ying; Liu, Dan; Hu, Chunxiang; Zhu, Ruixia (Frontiers in Immunology, 2024)
Myasthenia gravis (MG) stands as a perplexing autoimmune disorder affecting the neuromuscular junction, driven by a multitude of antibodies targeting postsynaptic elements. However, the mystery of MG pathogenesis has yet to be completely uncovered, and its heterogeneity also challenges diagnosis and treatment. Growing evidence shows the differential expression of non-coding RNAs (ncRNAs) in MG has played an essential role in the development of MG in recent years. Remarkably, these aberrantly expressed ncRNAs exhibit distinct profiles within diverse clinical subgroups and among patients harboring various antibody types. Furthermore, they have been implicated in orchestrating the production of inflammatory cytokines, perturbing the equilibrium of T helper 1 cells (Th1), T helper 17 cells (Th17), and regulatory T cells (Tregs), and inciting B cells to generate antibodies. Studies have elucidated that certain ncRNAs mirror the clinical severity of MG, while others may hold therapeutic significance, showcasing a propensity to return to normal levels following appropriate treatments or potentially foretelling the responsiveness to immunosuppressive therapies. Notably, the intricate interplay among these ncRNAs does not follow a linear trajectory but rather assembles into a complex network, with competing endogenous RNA (ceRNA) emerging as a prominent hub in some cases. This comprehensive review consolidates the landscape of dysregulated ncRNAs in MG, briefly delineating their pivotal role in MG pathogenesis. Furthermore, it explores their promise as prospective biomarkers, aiding in the elucidation of disease subtypes, assessment of disease severity, monitoring therapeutic responses, and as novel therapeutic targets.